(untitled) (Development Service Industry Management, 2025)
The article analyzes the dynamics of entrepreneurial activity in the rural tourism sector of Podillia in 2015–2023, emphasizing its role as a driver of local economic diversification and community development. The research focuses on the quantitative growth of rural guesthouses, changes in tourist flows, and income levels of small businesses in Khmelnytskyi, Vinnytsia and partly Ternopil regions. It is shown that the number of registered rural tourism homesteads increased from 84 in 2015 to 193 in 2023, while the average number of tourists per homestead more than doubled, and estimated average income per homestead grew by over 200%. These trends indicate the gradual institutionalization of rural tourism as a form of self-employment and micro-entrepreneurship in the region. The study identifies key factors behind this growth, including rising demand for domestic, ecological and individualized travel, the rich natural and cultural potential of Podillia, as well as the progressive integration of entrepreneurs into the digital environment and cluster-type cooperation at the community level. At the same time, a range of systemic barriers to entrepreneurial development in rural tourism is revealed. Among them are the lack of a clear legal status for rural homesteads, complex licensing and registration procedures, insufficient transport and communal infrastructure, limited access to financial resources, and a deficit of professional, managerial and marketing competences among owners. Using statistical, comparative and SWOT analysis, as well as content analysis of online representations of homesteads, the article substantiates that solving these problems requires coordinated actions of local authorities, business and educational institutions. Promising directions for intensifying entrepreneurial activity are proposed: implementation of regional and local programs to support rural tourism, integration of homesteads into tourist routes and branded products, development of territorial clusters and cooperatives, expansion of training and mentoring programs, and wider use of grant and microcredit instruments. The results of the study can be used for designing evidence-based strategies and policy measures aimed at transforming rural tourism in Podillia into a sustainable and competitive sector of the regional economy.